Refractory symptoms in paediatric palliative care: can ketamine help? - Franca Benini; Sabrina Congedi; Luca Giacomelli; Simonetta Papa; Aashni Shah; Gregorio Milani (BioExcel Publishing Ltd, 2021)
Background: One of the main challenges for paediatric palliative care (PPC) is the management of concomitant, different and severe symptoms that frequently affect the quality of life of PPC patients and are often refractory to commonly used pharmacological treatments. Consequently, many efforts are still needed to find the best therapeutic options to handle these refractory conditions. Since the first synthesis of ketamine in the 1960s, its pharmacokinetic and pharmacodynamic properties have been largely investigated and its potential wide range of clinical applications has become clear. However, this molecule still receives poor attention in some areas, including in children and PPC. This narrative review analyses the use of ketamine in children and the potential extension of its applications in PPC in order to provide new options for treatment in the PPC setting. Methods: Scientific papers published before October 2020 on MEDLINE, EMBASE and the Cochrane Library were considered. The cited references of the selected papers and the authors' personal collections of literature were reviewed. The terms "palliative care", "ketamine", "neuropathic pain", "procedural pain", "status epilepticus", "refractory pain" and "child", adding "age: birth-18 years" on a further filter were used for the search. Discussion: The use of ketamine in PPC should be more widely considered due to its overall favourable safety profile and its efficacy, which are supported by an increasing number of studies, although in settings different from PPC and of mixed quality. Ketamine should be proposed according to a case-by-case evaluation and the specific diagnosis and the dosage and route of administration should be tailored to the specific needs of patients. Furthermore, there is evidence to suggest that ketamine is safe and efficacious in acute pain. These findings can prompt further research on the use of ketamine for the treatment of acute pain in PPC. Conclusion: Ketamine could be a suitable option after the failure of conventional drugs in the treatment of different refractory conditions in PPC.